Opportunities for Improved Serodiagnosis of Human Tuberculosis, Bovine Tuberculosis, and Paratuberculosis. (6th June 2012) - Wadhwa, Ashutosh; Hickling, Graham J.; Eda, Shigetoshi
Abstract : Mycobacterial infections—tuberculosis (TB), bovine tuberculosis (bTB), and Johne's disease (JD)—are major infectious diseases of both human and animals. Methods presently in use for diagnosis of mycobacterial infections include bacterial culture, nucleic acid amplification, tuberculin skin test, interferon- γ assay, and serology. Serological tests have several advantages over other methods, including short turn-around time, relatively simple procedures, and low cost. However, current serodiagnostic methods for TB, bTB and JD exhibit low sensitivity and/or specificity. Recent studies that have aimed to develop improved serodiagnostic tests have mostly focused on identifying useful species-specific protein antigens. A review of recent attempts to improve diagnostic test performance indicates that the use of multiple antigens can improve the accuracy of serodiagnosis of these mycobacterial diseases. Mycobacteria also produce a variety of species-specific nonprotein molecules; however, only a few such molecules (e.g., cord factor and lipoarabinomannan) have so far been evaluated for their effectiveness as diagnostic antigens. For TB and bTB, there has been recent progress in developing laboratory-free diagnostic methods. New technologies such as microfluidics and "Lab-on-Chip" are examples of promising new technologies that can underpin development of laboratory-free diagnostic devices for these mycobacterial infections.